2021
DOI: 10.1149/1945-7111/ac3ff4
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Ozone Generation Using Compacted High Pressure High Temperature Synthesized Boron Doped Diamond Microparticle Electrodes

Abstract: Electrochemical ozone production (EOP) from water is an attractive, green technology for disinfection. Boron doped diamond (BDD) electrodes, grown by chemical vapor deposition (CVD), have been widely adopted for EOP due to their wide anodic window in water and excellent chemical and electrochemical stability. High pressure high temperature (HPHT) synthesis, an alternative growth technique used predominantly for the high-volume synthesis of nitrogen doped diamond microparticles, has been seldom employed for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…For many technological applications, the most common approach to growing diamond is via the process of chemical vapor deposition (CVD) 4 . Whilst high pressure, high temperature (HPHT) synthesis has also found use, it can be difficult to control impurity content via HPHT 5 , hence the preferred use of CVD-grown crystals in many technological applications 6 . For large-area applications, it is much cheaper to grow polycrystalline diamond (PCD) than singlecrystal diamond (SCD); PCD has numerous industrial applications, such as in thermal management 7 and electrochemistry.…”
mentioning
confidence: 99%
“…For many technological applications, the most common approach to growing diamond is via the process of chemical vapor deposition (CVD) 4 . Whilst high pressure, high temperature (HPHT) synthesis has also found use, it can be difficult to control impurity content via HPHT 5 , hence the preferred use of CVD-grown crystals in many technological applications 6 . For large-area applications, it is much cheaper to grow polycrystalline diamond (PCD) than singlecrystal diamond (SCD); PCD has numerous industrial applications, such as in thermal management 7 and electrochemistry.…”
mentioning
confidence: 99%
“…For most electrochemical applications, polycrystalline diamond is used. The diamond electrode is commonly grown via chemical vapor deposition (CVD), , as opposed to high-pressure, high-temperature synthesis. Depending on CVD growth conditions, the (110) facet typically grows faster than the (111) and (100) facets. In polycrystalline samples, which are typically cheaper to grow than single-crystal samples for large-area technological applications, the (110) facets can be revealed by mechanically polishing to a surface roughness where the surface is predominantly (110)-textured, as has been experimentally demonstrated using electron backscatter diffraction and STEM .…”
Section: Methodsmentioning
confidence: 99%
“…For most electrochemical applications, polycrystalline diamond is used. The diamond electrode is commonly grown via chemical vapor deposition (CVD), 93,94 as opposed to high-pressure, high-temperature 95 synthesis. Depending on CVD growth conditions, the (110) facet typically grows faster than the (111) and (100) facets.…”
Section: Construction Of Structuresmentioning
confidence: 99%
“…Recently, it has been shown that aluminium diboride (AlB 2 ) can be used as both a boron source and as an agent to remove nitrogen during the HPHT growth process. This process results in the growth of BDD particles, as small as 80 μm in size and doped with enough boron > 10 20 B atoms cm − 3 [5] to demonstrate metal-like electrochemical behaviour [6,7].…”
Section: Introductionmentioning
confidence: 99%